The wisdom of M. Montaigne in the book «Essais» - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The subject of this article is the reconstruction of ideas about the wisdom of life of M. Montaigne. It analyses Montaigne’s ideas about a happy life and ways to achieve it, his thoughts about reasonable strategy and tactics of life. The characteristics of the leading aspirations and passions of a person are given. Reflections on moral problems are highlighted, at the epicenter of which are judgments about goodness, conscience and ways of approaching a virtuous life. It is shown that his reasoning on the topic of human freedom is closely related to issues of morality. Skepticism is considered as a method of cognition characteristic of M. Montaigne.